Experimental study of brine discharge in coastal waters - Tay, Serene Ru-Wen. (2010)
With the global fresh water supply diminishing, developments to desalination technologies have been done to allow it to be more economically viable. Desalination is a process which separates brine and fresh water. However, this would also lead to many environmental problems which could disrupt the ocean biodiversity. To ensure brine is disposed properly, it is essential to study the dilution and mixing characteristics of it.